The genetic and molecular pathogenesis of myelodysplastic syndromes. (12th July 2018) - Shallis, Rory M.; Ahmad, Rami; Zeidan, Amer M.
Abstract: Myelodysplastic syndromes (MDS) comprise a diverse group of clonal and malignant myeloid disorders characterized by ineffective hematopoiesis, resultant peripheral cytopenias, and a meaningful increased risk of progression to acute myeloid leukemia. A wide array of recurring genetic mutations involved in RNA splicing, histone manipulation, DNA methylation, transcription factors, kinase signaling, DNA repair, cohesin proteins, and other signal transduction elements has been identified as important substrates for the development of MDS. Cytogenetic abnormalities, namely those characterized by loss of genetic material (including 5q‐ and 7q‐), have also been strongly implicated and may influence the clonal architecture which predicts such mutations and may provoke an inflammatory bone marrow microenvironment as the substrate for clonal expansion. Other aspects of the molecular pathogenesis of MDS continue to be further elucidated, predicated upon advances in gene expression profiling and the development of new, and improved high‐throughput techniques. More accurate understanding of the genetic and molecular basis for the development of MDS directly provides additional opportunity for treatment, which to date remains limited. In this comprehensive review, we examine the current understanding of the molecular pathogenesis and pathophysiology of MDS, as well as review future prospects which may enhance this understanding, treatment strategies, and hopefully outcomes.